Bilateral ovarian metastases of gallbladder carcinoma - a case report - Ljuština Saša; Milenković Svetlana; Maksimović Ružica; Kadija Saša; Sparić Radmila (Vojnosanitetski Pregled)
Introduction. Gallbladder carcinoma is a rare malignancy with a poor prognosis because it is diagnosed late. There are only a few cases of ovarian metastasis from gallbladder carcinoma described in the literature. We presented a rare case of ovarian metastasis of gallbladder carcinoma and highlight the importance of differentiation between primary and metastatic ovarian tumors. Case report. A 55-year old women had cholecystectomy for suspected cholecystitis. However, histological findings showed invasive adenocarcinoma of her gallbladder. The patient refused further proposed treatment. Three months later, the same patient presented with abdominal pain and discomfort. Imaging diagnostic methods (magnetic resonance scan) showed no local tumour mass at the site of cholecystectomy, but large, bilateral, multilocular ovarian tumor of mixed consistency. During surgery, ovarian tumours and infiltration of omentum was found. A total abdominal hysterectomy with bilateral salpingo- oophorectomy and omentectomy was performed. Histological findings indicated adenocarcinoma but could not distinguish between a primary ovarian carcinoma and gallbladder metastatic tumor. An immunohistochemical examination clarified that the findings corresponded to metastatic ovarian adenocarcinoma from the gastrointestinal tract, i.e., adenocarcinoma originating from the gallbladder. Unfortunately, the patient did not successfully recover and died three months later. Conclusion. The presence of ovarian masses of unknown origin and a diagnostic dilemma between primary and metastatic tumor require careful clinical, radiological, intraoperative, and histological examination for the purpose of establishing a definitive diagnosis and providing optimal treatment.